2017
DOI: 10.1016/j.micron.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Repair of calvarial bone defects in mice using electrospun polystyrene scaffolds combined with β-TCP or gold nanoparticles

Abstract: Non-biodegradable porous polystyrene (PS) scaffolds, composed of microfibers, have been prepared by electrospinning for the reconstruction of large bone defects. PS microfibers were prepared by incorporating β-TCP grains inside the polymer or grafting gold nanoparticles surface functionalized with mercaptosuccinic acid. Cytocompatibility of the three types of scaffolds (PS, β-TCP-PS and Au-PS) was studied by seeding human mesenchymal stem cells. Biocompatibility was evaluated by implanting β-TCP-PS and Au-PS s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…FTIR (Figure ) characterization confirmed the presence of phenyl group from PS polymer (CC) with peaks located at 1600, 1492, and 1450 cm −1 . Peak located at 3026 cm −1 corresponds to stretch vibrations of CH on phenyl radicals .…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…FTIR (Figure ) characterization confirmed the presence of phenyl group from PS polymer (CC) with peaks located at 1600, 1492, and 1450 cm −1 . Peak located at 3026 cm −1 corresponds to stretch vibrations of CH on phenyl radicals .…”
Section: Resultssupporting
confidence: 61%
“…Through LAS AF Lite software, it was possible to determine PS particles size and an average diameter of 46.76 μm was calculated. FTIR (Figure 3) characterization confirmed the presence of phenyl group from PS polymer ( C C ) with peaks located at 1600, 1492, and 1450 cm −1 [27]. Peak located at 3026 cm −1 corresponds to stretch vibrations of C H on phenyl radicals [28].…”
Section: Ns-40116 Enzyme Immobilization Processmentioning
confidence: 84%
“…Furthermore, histological assessments revealed that RCP/β‐TCP increased the thickness of newly formed bone compared with RCP. Terranova et al showed that β‐TCP fine particles coupled with polymer fibers induced a stimulatory effect on osteoblasts to promote bone formation of mouse (Terranova et al, 2017). In general, it is considered that β‐TCP is phagocytized by macrophages and osteoclasts and provides Ca/P ions to regenerative regions (Arbez & Libouban, 2017; Arbez, Manero, Mabilleau, Libouban, & Chappard, 2019; Detsch et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The membrane may be formed from different materials with specific properties of biocompatibility, cytotoxicity, resorbability, or osteogenic capacity. Different polymers are available, as PCL, PCL associated with other materials as PLA, or other electrospun substances like polystyrene [ 39 , 40 ]. The size and the morphology of the nanofibers are the main parameters that can be controlled, by modulating for example the flow rate or the polymer concentration [ 5 ].…”
Section: Discussionmentioning
confidence: 99%